A DNA/HDAC dual‐targeting drug CY190602 with significantly enhanced anticancer potency - Chuan Liu; Hongyu Ding; Xiaoxi Li; Christian P Pallasch; Liya Hong; Dianwu Guo; Yi Chen; Difei Wang; Wei Wang; Yajie Wang; Michael T Hemann; Hai Jiang (EMBO Molecular Medicine)
Abstract Genotoxic drugs constitute a major treatment modality for human cancers; however, cancer cells' intrinsic DNA repair capability often increases the threshold of lethality and renders these drugs ineffective. The emerging roles of HDACs in DNA repair provide new opportunities for improving traditional genotoxic drugs. Here, we report the development and characterization of CY190602, a novel bendamustine‐derived drug with significantly enhanced anticancer potency. We show that CY190602's enhanced potency can be attributed to its newly gained ability to inhibit HDACs. Using this novel DNA/HDAC dual‐targeting drug as a tool, we further explored HDAC's role in DNA repair. We found that HDAC activities are essential for the expression of several genes involved in DNA synthesis and repair, including TYMS, Tip60, CBP, EP300, and MSL1. Importantly, CY190602, the first‐in‐class example of such DNA/HDAC dual‐targeting drugs, exhibited significantly enhanced anticancer activity in vitro and in vivo. These findings provide rationales for incorporating HDAC inhibitory moieties into genotoxic drugs, so as to overcome the repair capacity of cancer cells. Systematic development of similar DNA/HDAC dual‐targeting drugs may represent a novel opportunity for improving cancer therapy.